(untitled) (Scientific journal of the Fergana State University, 2023)
In the article the data on solubility of components in system chlorate of magnesium – triethanolammonium of phosphate – water investigated visually-by a polythermal method in a temperature interval from (-40,5oC) with up to 47,1 oC are resulted with.